Perkawinan Dini, Dampaknya Bagi Kesehatan Reproduksi: Literature Review - Endah Purda Listya; Nurul Fatimah Susanti; Hasrita Octaliana (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Early marriage is a global public health issue that has a significant impact on women's reproductive health. Child marriage has similarities in various places, namely marriage before the age of 18. It is often associated with low levels of education for girls, as well as various negative health impacts. This study aims to examine the effects of early marriage on reproductive health in women. The research design used is a literature review. Data searches used to search for literature reviews are PubMed and Science Direct, with the keywords early marriage and reproductive health. Data are selected based on inclusion and exclusion criteria. The results of the study from 6 journal articles analyzed showed that women who marry at an early age have a higher risk of experiencing pregnancy complications such as anemia, premature birth, and low birth weight babies. In addition, an increased prevalence of mental health disorders such as anxiety and depression was also found. Increasing education for adolescents is urgently needed to access information on reproductive health education and the impacts on adolescents who engage in early marriage.